Exploring rare entities of sinonasal tumours from diagnosis to treatment: case series - Priyadarshini, D. Ekta; Shetty, Vaishnavi; Jayasandeep, S.; Kumar S. , Sathish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Tumours arising from the nose and paranasal sinuses are diverse in nature and some are rarely reported in literature. Sinonasal tumours, though rare, represent a clinical challenge due to their complex presentation. Herein this case series studies about three unique cases of sinonasal masses i.e. sinonasal myxoma, esthesioneuroblastoma, follicular lymphoid hyperplasia which presented at our institution and their management. These nasal masses, presented with similar clinical features like nasal obstructions or with epistaxis, were diagnosed through clinical examinations, imaging, and histopathology, and were managed accordingly. Due to the delayed time of presentation in different age groups with common clinical features, the chances of misdiagnosis at an early stage are common. This necessitates for an early intervention and a multidisciplinary approach to manage such rare cases.